Pembagian Harta Akibat Perebutan Antara Ahli Waris Ditinjau Dari Perspektif Hukum Adat Suku Sikka Krowe, Kecamatan Bola, Kabupaten Sikka - Maria Marliana Nona Yeti; Sukardan Aloysius; Darius Mauritsius (Lembaga Pengembangan Kinerja Dosen, 2024)
Inheritance is wealth which can be a collection of assets and liabilities from the heir which is transferred to the heirs. In inheritance law, a principle applies, namely that if an heir dies then by law his rights and obligations immediately pass to his heirs. The division of inherited assets can have legal impacts in society which occurred in the Sikka Krowe Tribe community, specifically in Klotong Hamlet, Bura Bekor Village, Bola District, Sikka Regency between disputed heirs. The problem formulation of this research is 1. What are the reasons for the struggle between heirs? 2. What is the process for resolving property disputes between heirs? And 3. How is the distribution of assets resulting from struggles between heirs viewed from the customary law of the Sikka Krowe tribe, Bola District, Sikka Regency? This research is empirical legal research. The data sources in this research are primary and secondary data sources. Data management and analysis techniques are editing, classification and description, then the data obtained, both primary and secondary data, will be processed and analyzed by researchers based on the problem formulation. Based on the research results, the reason why there is a struggle between heirs in inherited land disputes is that the family does not know the exact status of ownership of the inherited land and the factor of poor communication between the two parties. Settlement of disputes or disputes Done through utun omok (gathering to find a way out) includes: presenting family parties, deliberation or mediation (kula babong), decision making, settlement and returning decisions to the parties in dispute. Distribution of land inheritance using a patrilineal kinship system, namely distribution that is directly given to sons as the main heirs and gets more inheritance.